Rancang Bangun Praktikum Instrumentasi Industri Pertanian Menggunakan Augmented Reality - Sukadiana Putra, Indra; Gede Manuaba, Ida Bagus; ., Linawati (Majalah Ilmiah Teknologi Elektro; Vol 20 No 1 (2021): (Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2021.v20i01.P03, 2021)
Augmented Reality technology applied in the world of education can make the learning process more effective and more efficient. This study built an augmented reality application by applying the marker based tracking method which was then applied to the industrial instrumentation practicum course at the Faculty of Agricultural Technology, Udayana University. This aims to make practicum more effective and efficient. The resulting application is then tested using 2 tests, namely usability testing using the Usability method with a Likert scale and comparison testing using the Paired Sample T-test method. Usability testing aims to determine an assessment of the usability level of the application. In this test, we get a reusability value of 73.5 from a scale of 0-100. These results can be interpreted that this application has a good usability value. Comparative testing using the Paired Sample T-test method aims to obtain information on the extent of the comparison of the understanding of each respondent before and after the application of augmented reality in industrial instrumentation courses. In this test, the Sig. (2-tailed) of 0,000 which is still below the threshold of the Paired Sample T-test, which is 0.05. So this research concludes that there is a real difference between the results before and after the respondents used the application. This study concludes that the functionality of using this application can be considered to replace the visit of industrial instrumentation practicum courses so that the implementation of practicum becomes more effective and efficient.